2011
DOI: 10.1183/09031936.00173410
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography and pulmonary function in children with common variable immunodeficiency

Abstract: High-resolution computed tomography (HRCT) may be useful to monitor lung disease in children with common variable immunodeficiency disorder (CVID). We evaluated interobserver agreement and correlation with pulmonary function tests (PFTs) for automated quantification and visual scoring of air trapping and airway wall thickening on HRCT in paediatric CVID patients.In a cohort of 51 children with CVID, HRCT was analysed visually and automated for presence of air trapping and airway wall thickening. PFTs were expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In this study we observed that the JAK inhibitors oclacitinib and tofacitinib exhibit broad anti-itch properties that appear linked to their inhibition of transient receptor potential cation channel subfamily V member 1 (TRPV1), a receptor known to play an important role in the transmission of both pain and itch. 4 To illustrate the involvement of TRPV1 in the anti-itch properties of JAK inhibitors, we used 3 different approaches: (1) in vitro calcium imaging in DRG neurons; (2) in vivo methods with a mouse model of itch and one of capsaicin-induced pain; and (3) TRPV1-transfected AD293 cells.…”
Section: Janus Kinase Inhibitors Display Broad Anti-itch Properties: mentioning
confidence: 99%
“…In this study we observed that the JAK inhibitors oclacitinib and tofacitinib exhibit broad anti-itch properties that appear linked to their inhibition of transient receptor potential cation channel subfamily V member 1 (TRPV1), a receptor known to play an important role in the transmission of both pain and itch. 4 To illustrate the involvement of TRPV1 in the anti-itch properties of JAK inhibitors, we used 3 different approaches: (1) in vitro calcium imaging in DRG neurons; (2) in vivo methods with a mouse model of itch and one of capsaicin-induced pain; and (3) TRPV1-transfected AD293 cells.…”
Section: Janus Kinase Inhibitors Display Broad Anti-itch Properties: mentioning
confidence: 99%
“…Low diffusing capacity of the lung for carbon monoxide (DLCO) was associated with bronchial wall thickening and linear opacities. In another study of a cohort of 51 children with CVID, the authors reported correlations between air trapping on CT scans and distal airway obstruction, as measured by FEF25-75% [168].…”
Section: Bronchiolitis Obliterans After Lung Transplantationmentioning
confidence: 99%
“…67 While no pediatric asthma studies are available, in other pediatric obstructive disease processes, HRCT correlates of small-airway disease are seen. 68,69 Partly due to the ionizing radiation hazards of repeated HRCT scanning, there is emerging interest in the use of hyperpolarized gases as contrast agents for MRI. When there is a ventilation defect, the helium-3 or xenon-129 does not fill the airspaces, leading to a dark area on an otherwise high signal throughout the lung.…”
Section: Radiologic Studiesmentioning
confidence: 99%